Synthesis of Hinokitiol Sulfonate Derivatives and Their Anti‐Oomycete and Nematicidal Activities. Issue 9 (29th August 2022) - Che, Zhiping; Liu, Yibo; Chen, Luyao; Xing, Puhou; Li, Xiangdong; Huang, Xiaobo; Liu, Shengming; Chen, Genqiang; Lin, Xiaomin; Tian, Yuee
Abstract: In order to explore novel natural product‐based anti‐oomycete and nematicidal agents, sixteen unreported 2‐sulfonyloxyhinokitiol derivatives were prepared using the principle of active splicing, and structurally confirmed by proton nuclear magnetic resonance ( 1 H‐NMR), carbon‐13 nuclear magnetic resonance ( 13 C‐NMR), high‐resolution mass spectrometry (HRMS), and melting point. Moreover, we evaluated the title compounds as anti‐oomycete and nematicidal agents against two serious agricultural pests of Phytophthora capsici and Meloidogyne incongnita . Among the sixteen hinokitiol esters tested: (1) Compounds 3a and 3m exhibited the most potent anti‐oomycete activity compared to zoxamide against P. capsici, and the median effective concentration (EC50 ) values of 3a, 3m, and zoxamide were 18.64, 21.11, and 23.15 mg/L, respectively; Further studies showed that the existence of seven membered ring and carbonyl group was the necessary condition for the high anti‐oomycete activity of hinokitiol. (2) Compounds 3n and 3p exhibited more promising nematicidal activity than hinokitiol, and the median lethal concentration (LC50 ) values of 3n, 3p and 1 against M. incongnita were 0.2111, 0.2079, and 0.3933 mg/L, respectively. This result will pave the way for further modification of hinokitiol to develop potential new fungicides and nematicides. Abstract :